Hypovolemic shock due to rectus sheath hematoma secondary to subcutaneous low molecular weight heparin: a case report - Guerra, Mariana; Coelho , Joana; Fortuna , Jorge (Acta Biomedica Atenei Parmensis, 2022)
Rectus sheath hematoma (RSH) is a rare clinical entity caused by the rupture of the epigastric arteries or the rectus abdominal muscle itself, leading to the accumulation of blood in this location. It is a potentially fatal condition that mimics an acute belly condition. It is crucial to identify and treat it early to avoid unfavourable outcomes. We present the case of an 85-year-old woman hospitalized for pneumonia and respiratory failure who developed refractory hypovolemic shock associated with an abdominal mass. Computed tomography with angiography was performed, which detected the presence of a large hematoma of the wall of both rectus abdominal.(www.actabiomedica.it)